Does small-sided-games` court area influence acute metabolic, perceptual, and physical performance of young elite basketball players? - Marcelino, P. R.; Aoki, M. S.; Arruda, A. F. S.; Freitas, C. G.; Mendez-Villanueva, A.; Moreira, A. (Biology of Sport, 2016)
The purpose of this study was to investigate the effect of court size on physical and physiological responses of young elite basketball players. Twelve male basketball players (18.6 ± 0.5 y; 88.8 ± 14.5 kg; 192.6 ± 6.5 cm) from an under-19 team performed two small-sided games (match) with different court areas (28x15 vs 28x9). The number of players (3x3) was kept the same in each game. The players performed a repeated-sprint ability test (RSA test) before and after each match. Blood lactate concentration was collected before (pre) and after (post) the matches, and session rating of perceived exertion (session-RPE) was answered 30 minutes after the match. Best and mean time in RSA test were not different between the 28x15 and the 28x9 match-conditions (p>0.05).A significant difference was observed for lactate concentration from pre to post-match (p<0.05) in both conditions (28x15 and 28x9); however there was no significant interaction bewteen conditions.A Similar session-RPE mean score(28x15: 7.2 ± 1.4 and 28x9: 6.6 ± 1.4) wasdetected for both conditions (p>0.05, ES=0.41). In summary, this study showed that the different court areas induced similar physical and physiological responses. The magnitude of these responses was comparable to the responses verified during official basketball matches. Although there was no significant difference in effort perception, players tended to perceive agreater effort in the larger court size.